Differential expression of human beta defensins in placenta and detection of allelic variants in the DEFB1 gene from HIV-1 positive mothers (2011)
ABSTRACT: Introduction: Low infection rates in neonates born to HIV-1-seropositive mothers highlight the existence of natural defense mechanisms in the maternal-fetal interface. Human beta defensins (HBDs) inhibit HIV-1 replication in vitro and their variants are associated with HIV-1 resistance/susceptibility. Objective: Levels of HBD mRNA expression in placentas were obtained from seropositive and healthy mothers to determine whether HIV-1 infection induces anti-viral factors. Materials and methods. HBD-1, -2 and -3 transcripts were quantified by real time RT-PCR, and A692G/G1654A/A1836G variants in the DEFB1 gene were evaluated by sequencing. Results: Transcript levels of HBD-1 were significantly higher, and those of HBD-3 were lower in placenta from seropositive mothers compared to controls. Additionally, simultaneous presence of the A692G A/G and A1836G G/G genotypes was associated with high expression of HBD-1 in all populations and the A692G variant in babies born to seropositive mothers was in Hardy-Weinberg disequilibrium. Conclusion: Contrasting results in levels of HBDs were probably due to viral stimuli and suggest that HIV-1 induce a differential expression of HBDs in placenta and these proteins could be involved in protecting against HIV-1 at least early in pregnancy. However, it was not possible to associate these findings directly with protection against HIV-1 vertical transmission since none of the newborn infants became infected.